Selective vulnerability of ARID1A deficient colon cancer cells to combined radiation and ATR-inhibitor therapy - Xu, Shan; Sak, Ali; Niedermaier, Ben; Erol, Yasin Bahadir; Groneberg, Michael; Mladenov, Emil; Kang, MingWei; Iliakis, George; Stuschke, Martin (Frontiers in Oncology, 2022)
ARID1A is frequently mutated in colorectal cancer (CRC) cells. Loss of ARID1A function compromises DNA damage repair and increases the reliance of tumor cells on ATR-dependent DNA repair pathways. Here we investigated the effect of ionizing radiation (IR), in combination with ATR inhibitors (ATRi) in CRC cell lines with sufficient and deficient ARID1A. The concept of selective vulnerability of ARID1A deficient CRC cells to ATRi was further tested in an ex vivo system by using the ATP-tumor chemosensitivity assay (ATP-TCA) in cells from untreated CRC patients with and without ARID1A expression. We found selective sensitization upon ATRi treatment as well as after combined treatment with IR (P<0.001) especially in ARID1A deficient CRC cells (P <0.01). Knockdown of ARID1B further increased the selective radiosensitivity effect of ATRi in ARID1A negative cells (P<0.01). Mechanistically, ATRi abrogates the G2 checkpoint (P<0.01) and homologous recombination (P<0.01) in ARID1A deficient cells. Most importantly, ex-vivo experiments showed that ATRi had the highest radiosensitizing effect in ARID1A negative cells from CRC patients. Collectively, our results generate pre-clinical and clinical mechanistic rationale for assessing ARID1A defects as a biomarker for ATR inhibitor response as a single agent, or in a synthetic lethal approach in combination with IR.